Antiperovskite Gd3SnC: Unusual Coexistence of Ferromagnetism and Heavy Fermions in Gd Lattice. Issue 37 (28th July 2021) - Bang, Joonho; Park, Jongho; Lee, Kimoon; Kim, Minsoo; Kyung, Wonshik; Denlinger, Jonathan D.; Kim, Yeongkwan; Lee, Young Hee; Kim, Changyoung; Kim, Sung Wng
Abstract: Inverted structures of common crystal lattices, referred to as antistructures, are rare in nature due to their thermodynamic constraints imposed by the switched cation and anion positions in reference to the original structure. However, a stable antistructure formed with mixed bonding characters of constituent elements in unusual valence states can provide unexpected material properties. Here, a heavy‐fermion behavior of ferromagnetic gadolinium lattice in Gd3 SnC antiperovskite is reported, contradicting the common belief that ferromagnetic gadolinium cannot be a heavy‐fermion system due to the deep energy level of localized 4f‐electrons. The specific heat shows an unusually large Sommerfeld coefficient of ≈ 1114 mJ mol −1 K −2 with a logarithmic behavior of non‐Fermi‐liquid state. It is demonstrated that the heavy‐fermion behavior in the non‐Fermi‐liquid state appears to arise from the hybridized electronic states of gadolinium 5d‐electrons participating in metallic GdGd and covalent GdC bonds. These results accentuate the unusual chemical bonds in CGd6 octahedra with the dual characters of gadolinium 5d‐electrons for the emergence of heavy fermions. Abstract : Electronically inverted structures with switched crystallographic positions of cations and anions from the original structure allow an exotic phenomenon to be accessed. Antiperovskite Gd3 SnC exhibits unusual coexistence of ferromagnetism and heavy fermions, contradicting the common belief that heavy‐fermion behavior cannot emerge in ferromagnetic 4f‐block elements. These unusual phenomena originate from the mixed bonding nature of antiperovskite structure.